The Solutions to Matrix Equation AX=B with Some Constraints - Chang-Zhou Dong; Yu-Ping Zhang (Journal of Applied Mathematics)
Let P be a given Hermitian matrix satisfying P2=I. Using the eigenvalue decomposition of P, we consider the least squares solutions to the matrix equation AX=B with the constraints PX=XP and X*=X. A similar problem of this matrix equation with generalized constrained is also discussed.